2016
DOI: 10.1007/s10901-016-9510-9
|View full text |Cite
|
Sign up to set email alerts
|

From income and housing wealth inequalities to emissions inequality: carbon emissions of households in China

Abstract: The emerging notion of emissions inequality expands the idea of sustainability by incorporating economic opportunity as well as social needs and rights into environ-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…In the current backdrop of increasing global apprehension about carbon emissions and their impact on climate change, considerable research effort has been devoted to exploring the intricate relationship between household characteristics, household consumption patterns and their environmental repercussions (Clarke-Sather et al ., 2011; Duro, 2013; Yang et al ., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the current backdrop of increasing global apprehension about carbon emissions and their impact on climate change, considerable research effort has been devoted to exploring the intricate relationship between household characteristics, household consumption patterns and their environmental repercussions (Clarke-Sather et al ., 2011; Duro, 2013; Yang et al ., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The cost of changing consumption towards "greener" goods and services can be higher than paying carbon taxes (as evidenced by the cost and length of train journeys that is often higher than flights to the same destination; or green mortgages in a context where energy efficient housing remains more costly than non-energy efficient one). Furthermore, the inducement of changes in consumption behaviour is less likely to include high-income groups, which have been identified as the higher CO2 emitters (Knight et al 2017;Gore, 2015;Yang et al 2017) and are paradoxically the ones who can afford to secure and maintain their carbon-intensive consumption patterns and lifestyle by "buying" their right to pollute. As a result, the 1 st dimension of GIP can have a discriminatory impact on low-income groups if they neglect issues of income distribution.…”
Section: First Dimension Of Gip: Consumption-focused Approaches To Cl...mentioning
confidence: 99%
“…The results showed that the properties of energy-saving buildings and better community facilities had significantly reduced the carbon emission levels of households. Residents of communities far away from public facilities tended to have a higher probability of buying cars, leading to higher traffic carbon emissions [ 15 ]. Gu found the CO 2 emission status of the energy consumption of urban households in Nanjing and its influencing factors were analyzed.…”
Section: Introductionmentioning
confidence: 99%